Inula Viscosa Extracts Induces Telomere Shortening and Apoptosis in Cancer Cells and Overcome Drug Resistance. (2nd January 2016) - Merghoub, Nawal; El Btaouri, Hassan; Benbacer, Laila; Gmouh, Saïd; Trentesaux, Chantal; Brassart, Bertrand; Terryn, Christine; Attaleb, Mohammed; Madoulet, Claudie; Benjouad, Abdelaziz; Amzazi, Saaïd; El Mzibri, Mohammed; et al.
ABSTRACT: Telomerase is activated in human papillomavirus (HPV) positive cervical cancer and targeting telomeres offers a novel anticancer therapeutic strategy. In this study, the telomere targeting properties, the cytotoxic as well as the pro-apoptotic effects of hexane (IV-HE) and dichloromethane (IV-DF) fractions from Inula viscosa L. extracts were investigated on human cervical HeLa and SiHa cancer cells. Our data demonstrate that IV-HE and IV-DF extracts were able to inhibit cell growth in HeLa and SiHa cells in a dose-dependent manner and studied resistant cell lines exhibited a resistance factor less than 2 when treated with the extracts. IV-HE and IV-DF extracts were able to inhibit telomerase activity and to induce telomere shortening as shown by telomeric repeat amplification protocol and TTAGGG telomere length assay, respectively. The sensitivity of fibroblasts to the extracts was increased when telomerase was expressed. Finally, IV-HE and IV-DF were able to induce apoptosis as evidenced by an increase in annexin-V labeling and caspase-3 activity. This study provides the first evidence that the IV-HE and IV-DF extracts from Inula viscosa L. target telomeres induce apoptosis and overcome drug resistance in tumor cells. Future studies will focus on the identification of the molecules involved in the anticancer activity.